A customer redirection rule for minimizing extra effort in bicycle-sharing systems - Lorenzo, Simon Anthony D.; Lorenzo, Lowell L.; Martinez, Iris Ann G. (Quezon City College of Engineering, University of the Philippines Diliman, 2019)
Bicycle sharing is a new type of transportation system that has been developing over the years. These systems tend to have low service levels if manual bike level balancing is not done, resulting to schemes such as static and dynamic bike repositioning, as well as customer redirection. While customer redirection allows for a high system service level, it asks customers to travel distances they would otherwise not need to. The study aims to produce a solution to the extra effort being asked from the customer by producing a rule that would minimize the said quantity, while still maintaining a target service level of the system. The proposed rule is an improvement on an existing rule for customer redirection developed by Aeschbach et al. It entails the redirection of both the customer's trip origin and destination, following certain criteria. However, instead of a redirection criterion that is fixed (as proposed by the aforementioned study), thresholds are now dynamic based on the stations forecasted supply and demand for bikes. This approach was obtained from the utility plateau concept discussed in the work of Ruch et al. A simulation model was used to evaluate the effectiveness of the proposed rule. Results show that the new rule was able to reduce the system average extra effort for customers by as much as 43.35% while maintaining the service level, over 100 replications of the simulation. Thus, the rule brought about by the study is the best among all existing rules, in terms of minimizing extra effort, as of the time of writing.
Thesis (Master of Science in Industrial Engineering)--University of the Philippines Diliman
Keywords: Bicycle trails; Bicycle sharing programs; Repositioning strategy